The Importance of Developing Rigorous Social Science Methods for Community Engagement and Behavior Change During Outbreak Response. (9th December 2021) - Ashworth, Henry C.; Dada, Sara; Buggy, Conor; Lees, Shelley
ABSTRACT: Despite growing international attention, the anthropological and socio-behavioral elements of epidemics continue to be understudied and under resourced and lag behind the traditional outbreak response infrastructure. As seen in the current 2019 coronavirus disease (COVID-19) pandemic, the importance of socio-behavioral elements in understanding transmission and facilitating control of many outbreak-prone pathogens, this is problematic. Beyond the recent strengthening of global outbreak response capacities and global health security measures, a greater focus on the socio-behavioral components of outbreak response is required. We add to the current discussion by briefly highlighting the importance of socio-behavior in the Ebola virus disease (EVD) response, and describe vital areas of future development, including methods for community engagement and validated frameworks for behavioral modeling and change in outbreak settings.